Multiparameter-based product, energy and exergy optimizations for biomass gasification. (1st November 2021) - Caglar, Basar; Tavsanci, Duygu; Biyik, Emrah
Graphical abstract: Highlights: Biomass gasification model via Gibbs free energy minimization approach. Synergetic effect of gasifying agents via a multiparameter optimization. The highest syngas yield is observed at T > 1100 K, SBR > 0.5 and/or CBR > 0.8. The top H2 yields are observed at high SBR, low CBR (<0.9) and 900–1150 K. CGE changes between 114% and 122% while exergy efficiency is between 77% and 86%. CO2 offers several advantages as a gasifying agent. Abstract: The thermodynamic modelling of biomass gasification was studied by using Gibbs free energy minimization approach. Different from the studies using the same approach, the simultaneous presence of all gasifying agents (air, H2 O and CO2 ) was considered and a multiparameter optimization was applied to determine the synergetic effect of gasifying agents for hydrogen, syngas with a specific H2 /CO ratio and methane production. The performance of gasification was assessed by using technical and environmental performance indicators such as product yields, cold gas efficiency, exergy efficiency, CO2 emission and the heat requirement of the gasifier. The results show that the simultaneous presence of gasifying agents does not create considerable changes in syngas yield, H2 yield, methane yield, CGE and exergy efficiency while it allows to tune the H2 /CO ratio and the heat requirement of the gasifier. The highest syngas yield is observed at T > 1100 K and 1 bar and when SBR > 0.5 and/or CBR > 0.8 with the absence of air, at which CGE changes between 114% and 122% while exergy efficiency is between 77% and 86%. The results prove that CO2 offers several advantages as a gasifying agent and suggests that CO2 recycling from gasifier outlet is a useful option for the biomass gasification.